(untitled) (World Economics and Finance Bulletin, 2026)
This research discusses the role of marketing information systems and their impact on the decisions of organizations or economic units. The importance of this marketing system is evident in the support it provides to management and decision-makers within the economic unit, as information is the primary factor in achieving success amidst rapidly evolving circumstances. The existence of modern technology and communication methods has shortened distances between the world and placed everything new at the fingertips of those who seek it with ease. Consequently, every institution or economic unit must keep pace with the current situation and compete with its counterparts in obtaining marketing information to achieve innovation, find new distribution and marketing channels, and use advanced technology that meets customer requirements, thus ensuring the institution’s continuity and the achievement of its goals and successes. Therefore, this research addresses a set of concepts related to marketing information systems, including the concepts of decision, information, systems, and marketing, and then the link between these concepts and their impact on marketing information systems, which is reflected in their influence on decisionmaking for the economic unit based on the available information that the institution works with. The research also addresses the concept of marketing, its importance, and its direct relationship to information systems and the decisions made by the individual or group that has the authority to make decisions in order to keep pace with the institution’s continuity and achieve the set goals.